Attitudes towards Open Access Books in the European Research Area - Gabriela Manista; Maciej Maryl; Magdalena Wnuk (Liber Quarterly: The Journal of European Research Libraries)
This paper examines the challenges and opportunities of publishing Open Access (OA) books within the European Research Area (ERA), drawing on data collected through the PALOMERA project. Despite the growing interest in OA books, the landscape remains fragmented due to a lack of clear policies. National policies are often sparse, with institutional and funder mandates typically focused on journal articles rather than monographs. An issue also highlighted is the marginalisation of non-English language works, which receive significantly less visibility than English-language publications. Additionally, the perceived prestige of OA monographs remains a concern, with some scholars viewing them as less reputable than traditionally published works. This paper synthesises findings from 42 in-depth interviews to offer an overview of the current state of OA book publishing in Europe. It identifies areas for policy improvement to foster a more inclusive and sustainable OA landscape.